Hypospadias surgery: a single centre study to compare different techniques with special emphasis on transverse prepucial onlay island flap urethroplasty - Mishra, Atul (International Surgery Journal, 2020)
Background: Urethroplasty for hypospadias is a difficult surgery in the best of hands. One stage surgery is usually preferred for its multiple benefits. Many techniques exist each with its own merits and demerits. Aim of the study was to compare different techniques in hypospadias surgery with special emphasis on transverse prepucial onlay island flap urethroplasty. Methods: All children operated for hypospadias from the period of 2016-2019 in Department of Surgery at Geetanjali Medical College and Hospital, Udaipur were included in the group after obtained approval from institutional ethical clearance commitee. The technique to be used was decided on a case to case basis depending mainly on the position of the meatus, size of the urethral plate and chordee (ventral curvature). All patients were analyzed for various complications and overall success rate. Results: 77 patients were operated and analyzed. Overall the study could not establish the superiority of one technique above another. At the same time it establishes the versatility, satisfactory results and low complication rate of transverse prepucial onlay island flap (TPOIF) in different types of hypospadias. Conclusions: Success in urethroplasty depends on proper case selection, meticulous technique, a buttressing layer wherever possible and that TPOIF is a versatile technique for single stage hypospadias repair in distal, mid and proximal penile hypospadias.